Editorial Introduction: Global competence, decolonization, and Asian educational philosophies - Hebert, David G. (Nordic Journal of Comparative and International Education (NJCIE), 2021)
The articles in this special issue on “New Perspectives on Asian Educational Philosophies” offer a comparative perspective to explain the educational philosophies of notable Asian thinkers who tend to be little recognized in Europe. Arguments associated with decolonization offer one timely rationale for our work, but our purpose with this special issue is not so much about convincing readers that change is necessary, but rather to offer specific resources for diversification of higher education curricula. We assume that as years pass, educators will increasingly seek to know more about educational thought from across the world.